1982
DOI: 10.1038/hdy.1982.51
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance and mapping of storage protein genes in Pisum sativum L.

Abstract: SUMMARYOne and two-dimensional sodium dodecyl sulphate polyacrylamide gel electrophoretic techniques have been used to follow the inheritance of legumin and convicilin subunits in crosses of various pea lines. The major legumin acidic subunits behaved as products of a single Mendelian gene with at least five different possible alleles. Independent segregation of a minor "big" legumin acidic subunit and the acidic and basic subunits of "small" legumin were observed, suggesting that while the main legumin subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 17 publications
2
28
1
Order By: Relevance
“…4, arrows). These differences can be expected among the various genera, in view of the variant subunit forms which have been observed intraspecifically, for example, with pea (12,23) and oat (17) globulins. Such variability might also be expected to contribute to heterogeneity at the holoprotein level as shown to exist in pea (24) and soybean (9,20).…”
Section: Discussionmentioning
confidence: 99%
“…4, arrows). These differences can be expected among the various genera, in view of the variant subunit forms which have been observed intraspecifically, for example, with pea (12,23) and oat (17) globulins. Such variability might also be expected to contribute to heterogeneity at the holoprotein level as shown to exist in pea (24) and soybean (9,20).…”
Section: Discussionmentioning
confidence: 99%
“…Marker afp9i is located 13 cM from the k gene, which was found by Matta and Gatehouse (1982) to be linked (approx. 3 cM) to a gene coding convicilin, a storage protein (Cvc).…”
Section: Individual Qtl Effectsmentioning
confidence: 99%
“…Elucidation of the synthesis of vicilin has shown that the initial products of the vicilin structural genes are 50,000 Mr precursors, of differing amino acid sequences, some of which are proteolytically cleaved after translation is complete to yield the "subunits" or component polypeptides of Mr < 35,000 observed in the protein as isolated (Gatehouse et a!., , 1982. Variation in the 50,000 Mr subunits of vicilin is thus most likely to reflect variation in the structural genes for the protein rather than to be a result of post-translational modification (which may not be simply related to protein structure).…”
Section: Introductionmentioning
confidence: 99%
“…Lg-1) (Davies, 1980); Matta and Gatehouse, 1982). The latter authors also reported the mapping of the genetic locus for the storage protein related to vicilin, convicilin (Cvc), to a segment of chromosome 2 on the pea genome (s. 18• Cvc 3 k) where s is the locus determining "sticky" (s) or "non-sticky" (S) seeds ("sticky" seeds adhere together in the pod), and k is the locus determining normal (K) or keel-like (k) wings on the flowers.…”
mentioning
confidence: 99%